Strategi Peningkatan Laba Penjualan Melalui Pelatihan Penyusunan Harga Pokok Jual Di Paguyuban Ternak Rakyat Indonesia Desa Buluharjo Kabupaten Magetan - La Ode Abdullah; Yana Dwi Christanti; Yopie Diondy Kurniawan; Amri Amrulloh (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Some small and medium business actors, especially breeders in the Indonesian People's Livestock Association, Buluharjo Village, Plaosan District, Magetan Regency, do not understand how to prepare the cost of goods sold for their livestock business so that the selling price is determined only by considering market prices, resulting in relatively minimal income. when compared with financial and non-financial expenses. They do not realize that many costs have been incurred but have not been taken into account, so even though the selling price is quite high and in accordance with market value, it has not been able to fully cover operational expenses. To provide a solution to this problem, it is necessary to have Training on the Preparation of Cost of Goods Sold as a Consideration for Setting Selling Prices in Maximizing Sales Profits at the Indonesian People's Livestock Association, Buluharjo Village, Plaosan District, Magetan Regency so that livestock business actors can be more effective in calculating their financial management. The training method carried out with Lecture-style training (Lecture) can be a very valuable resource for communicating the necessary information quickly and the Independent Self-study method, this method is expected to be able to train oneself by studying the material that has been given . In addition, this method was chosen because it took into account the distance and time constraints of the presenters and training participants, so that participants were given a simple report format in preparing cost of goods sold. In organizing activities, participants actively ask questions and discuss the conditions and limitations in the preparation of Cost of Goods Sold until the training is complete